2022
DOI: 10.1080/10495398.2022.2105228
|View full text |Cite
|
Sign up to set email alerts
|

Salivary cell-free HSD17B1 and HSPA1A transcripts as potential biomarkers for estrus identification in buffaloes ( Bubalus bubalis )

Abstract: Background: Estrus detection is a major problem in buffaloes because of the poor expression of estrus signs leading to low reproductive e ciency. Salivary transcripts analysis is a promising tool to identify biomarker; therefore, the present study was carried out to evaluate their potential as estrus biomarker.Methods: The levels of HSD17B1, INHBA, HSPA1A, Testin transcripts were compared in saliva during estrous cycle stages [early proestrus (day -2, EP), late proestrus (day-1, LP), estrus (E), metestrus (ME)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The transcripts of lactoferrin (LF) and glutamate receptor-interacting protein 1 (GRIP1) were highly expressed in the uterine tissue of cattle during the estrus when compared to other stages of the estrous cycle [44]. Likewise, higher expression of mRNA transcripts of HSD17B1 and heat shock 70-kDa protein 1A (HSPA1A) in saliva during the estrus stage in both cyclic heifers and pluriparous buffaloes was reported [45]. In yet another study, it was reported that the mRNA transcript of tissue inhibitors of metalloproteinase 1 (TIMP1) was significantly over-expressed in cell free saliva at the estrus stage when compared to the diestrus stage in buffaloes [46].…”
Section: Differential Expression Of Mrna Transcripts At Estrus Stagementioning
confidence: 99%
See 1 more Smart Citation
“…The transcripts of lactoferrin (LF) and glutamate receptor-interacting protein 1 (GRIP1) were highly expressed in the uterine tissue of cattle during the estrus when compared to other stages of the estrous cycle [44]. Likewise, higher expression of mRNA transcripts of HSD17B1 and heat shock 70-kDa protein 1A (HSPA1A) in saliva during the estrus stage in both cyclic heifers and pluriparous buffaloes was reported [45]. In yet another study, it was reported that the mRNA transcript of tissue inhibitors of metalloproteinase 1 (TIMP1) was significantly over-expressed in cell free saliva at the estrus stage when compared to the diestrus stage in buffaloes [46].…”
Section: Differential Expression Of Mrna Transcripts At Estrus Stagementioning
confidence: 99%
“…Studies on differential expression of mRNA transcripts [44][45][46], heat shock proteins [47][48][49][50] and other proteins [44,[51][52][53][54] in various biological fluids and/or tissues collected at different stages of estrous cycle have been reported and the use of the same as biomarkers for the identification of estrus has been opined.…”
Section: Differential Expression Of Mrna and Proteins During Various ...mentioning
confidence: 99%